Resistência e reafirmação camponesa: transformações e permanências na agricultura no município de Faina/GO - Silva, Aelton Brito [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis analyzes the forms of resistance that small farmers in the municipality of Faina / GO have developed to withstand transformations stimulated by policies of agricultural modernization since the 1970s. The study uses a comparative approach to chart production and lifestyle transformations between two generations of peasant families in Faina, a small rural community located near the historic colonial city of Goiás Velho. It argues that modernization policies have provoked transformations in production processes and the relations of production, thus altering the way of life of peasant farmers and the composition of their territory. In addition to bibliographical and documentary research, a geo-historical questionnaire was used to generate data from affected families. Responses were gathered through interviews, which also stimulated the collection of oral histories, covering seven peasant families organized in the municipality by the Movement of Small Farmers - MPA, which has worked to reaffirm their peasant identity

Analisa as transformações recentes na agricultura no município de Faina/GO, a partir dos anos 1970 quando houve um impulso no processo de modernização agrícola em Goiás. O processo estimulou transformações que mudaram as formas de produzir e as relações de produção, alterando assim o modo de vida dos camponeses e a composição de seus territórios. Foi feito uma análise comparativa entre o campo produtivo das famílias camponesas da atualidade e a geração anterior - a dos pais delas - a fim de compreender as transformações e permanências do território em consequência do processo de modernização agrícola. Para tanto, além da pesquisa bibliográfica e documental, foi utilizada pesquisa descritiva e exploratória de caráter qualitativa com aplicação de questionários e a gravação de entrevistas semiestruturadas, abrangendo sete famílias camponesas organizadas no Movimento dos Pequenos Agricultores - MPA -, no município de Faina/GO
Keywords: Geografia; Agricultura; Agricultura e tecnologia; Camponeses - Goiás (GO); Territorio nacional - Goiás (GO); Geography